2002
DOI: 10.1183/09031936.02.00094202
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of anti-inflammatory and clinical effects of beclomethasone dipropionate and salmeterol in moderate asthma

Abstract: Inhaled corticosteroids and long-acting b 2 -agonists effectively control asthma symptoms and improve airway function. The effects of beclomethasone were compared with those of salmeterol on markers of eosinophilic inflammation in induced sputum in steroid-naïve asthmatic subjects with moderate asthma.Fifteen moderate asthmatics were treated with either beclomethasone dipropionate (500 mg b.i.d) or salmeterol (50 mg b.i.d) for 4 weeks, according to a randomised, double-blind, parallel-group study design. All p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 29 publications
0
11
1
Order By: Relevance
“…We decided to treat most patients with salmeterol, and not just with rescue salbutamol, in order to maintain a long‐lasting improvement in symptoms, without treating eosinophilic inflammation. The absence of a significant anti‐inflammatory effect of long‐acting beta2‐agonists is controversial; some investigators have observed minimal changes in airway inflammatory markers after salmeterol or formoterol treatment, 28,29 whereas other studies have shown no effect on sputum eosinophil numbers 7,30 . Therefore, in keeping with current guidelines, 1 we considered salmeterol to be devoid of significant anti‐inflammatory activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We decided to treat most patients with salmeterol, and not just with rescue salbutamol, in order to maintain a long‐lasting improvement in symptoms, without treating eosinophilic inflammation. The absence of a significant anti‐inflammatory effect of long‐acting beta2‐agonists is controversial; some investigators have observed minimal changes in airway inflammatory markers after salmeterol or formoterol treatment, 28,29 whereas other studies have shown no effect on sputum eosinophil numbers 7,30 . Therefore, in keeping with current guidelines, 1 we considered salmeterol to be devoid of significant anti‐inflammatory activity.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in keeping with current guidelines, 1 we considered salmeterol to be devoid of significant anti‐inflammatory activity. We have previously demonstrated an acute effect of salmeterol on allergen‐induced eosinophilic inflammation; 31 however, this effect was lost after short‐term regular treatment with salmeterol alone 7,14 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When an individual who has no history of first-line TB treatment develops MDR-TB, it is termed primary. When insufficient treatment leads to selection of spontaneously resistant strains (i.e., drug resistance is acquired), the disease is termed secondary MDR-TB [2]. …”
Section: Introductionmentioning
confidence: 99%
“…Eosinophil Cationic Protein (ECP) and Myeloperoxidase (MPO) are granulocyte proteins that are well correlated with eosinophil cell count [18] and decrease after anti-nflammatory treatment [19,20].…”
Section: Fluid-phase Mediatorsmentioning
confidence: 99%